The Use of Artificial Intelligence (AI)-Based Applications to Improve Learning Focus in Children with ADHD: A Systematic Literature Review - Hardiani, Wahyu; Lianty, Leliana; Yunitasari, Septiyani Endang; Novita, Kholifatul; Mursita, Rohmah Ageng (Eligible : Journal of Social Sciences, 2025)
Children with Attention Deficit Hyperactivity Disorder (ADHD) often experience difficulties in maintaining attention and focus during learning activities. The advancement of technology, particularly Artificial Intelligence (AI), has opened new opportunities to support more adaptive and individualized educational interventions for children with ADHD. This article aims to review recent studies on the utilization of AI-based applications to improve learning focus among children with ADHD. The method employed is a literature review by examining scientific articles obtained from several online databases, including Google Scholar, PubMed, Scopus, ScienceDirect, and ERIC, within the publication range of 2018 to 2024. Inclusion criteria consist of peer-reviewed articles in English or Indonesian that specifically discuss the use of AI applications to enhance attention in children with ADHD. The findings reveal that AI-powered applications, such as adaptive educational games, digital therapies, and cognitive training systems, hold great potential in improving focus and reducing symptoms of inattention and impulsivity. However, certain limitations, such as technological accessibility, device dependency, and data privacy issues, remain challenges that must be addressed. This review concludes that the integration of AI technology into the learning process of children with ADHD is a promising strategic approach, yet it requires ethical, inclusive, and evidence-based implementation.